The Effect of Work Motivation, Work-Life Balance, and Work Environment on Performance Ambon City Population and Civil Registration Office - Souhoka, Semuel (Eastasouth Institute, 2025)
This study aims to analyze the influence of work motivation, work-life balance, and work environment on employee performance at the Population and Civil Registration Office of Ambon City. The study used a quantitative approach with multiple linear regression, and the entire population of 43 employees was sampled (total sampling). The results of the classical assumption test showed that the data were free from multicollinearity, heteroscedasticity, and normally distributed. Regression analysis showed that the three independent variables partially and simultaneously had a significant effect on employee performance (R² = 0.940). Work motivation had the largest influence, followed by work-life balance and work environment. These findings confirm that increasing motivation, work-life balance, and managing a conducive work environment are effective strategies for improving employee performance.